Solutions to the Schrödinger Equation: Nonlocal Terms and Geometric Constraints - Irina Petreska; Pece Trajanovski; Trifce Sandev; Jonathan A. M. Almeida Rocha; Antonio Sérgio Magalhães de Castro; Ervin K. Lenzi (Mathematics)
Here, we investigate a three-dimensional Schrödinger equation that generalizes the standard framework by incorporating geometric constraints. Specifically, the equation is adapted to account for a backbone structure exhibiting memory effects dependent on both time and spatial position. For this, we incorporate an additional term in the Schrödinger equation with a nonlocal dependence governed by short- or long-tailed distributions characterized by power laws associated with Lévy distributions. This modification also introduces a backbone structure within the system. We derive solutions that reveal various behaviors using Green’s function approach expressed in terms of Fox H-functions.